2021
DOI: 10.3390/ph15010054
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Sodium Dodecyl Sulfate Complexes for Microencapsulation of Vitamin E and Its Release Profile—Understanding the Effect of Anionic Surfactant

Abstract: Microencapsulation of bioactive substances is a common strategy for their protection and release rate control. The use of chitosan (Ch) is particularly promising due to its abundance, biocompatibility, and interaction with anionic surfactants to form complexes of different characteristics with relevance for use in microcapsule wall design. In this study, Ch/sodium dodecyl sulfate (SDS) microcapsules, without and with cross-linking agent (formaldehyde (FA) or glutaraldehyde (GA)), were obtained by the spray dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…For example, strain-induced polymer crystallization could be applied to mechanically condition CHT, as done commonly with vulcanized rubber, and some polysaccharides. 53 The strain-induced restructuring of SDS micelles could potentially be coupled with SDS's effectiveness in encapsulating a variety of payloads, 27,29,54 similar to previously reported tensile strain-sensing membranous drug delivery systems. 55 These insights may also be relevant to improving the properties of food products, cosmetics, and other consumer products, where SDS:CHT and other polysaccharide−surfactant combinations are routinely used.…”
Section: ■ Conclusionsupporting
confidence: 67%
“…For example, strain-induced polymer crystallization could be applied to mechanically condition CHT, as done commonly with vulcanized rubber, and some polysaccharides. 53 The strain-induced restructuring of SDS micelles could potentially be coupled with SDS's effectiveness in encapsulating a variety of payloads, 27,29,54 similar to previously reported tensile strain-sensing membranous drug delivery systems. 55 These insights may also be relevant to improving the properties of food products, cosmetics, and other consumer products, where SDS:CHT and other polysaccharide−surfactant combinations are routinely used.…”
Section: ■ Conclusionsupporting
confidence: 67%
“…26,27 Studies have shown that different coacervates tend to exhibit distinct morphologies and rheological properties, with “coacervates” providing a smooth sensation and “precipitates” imparting a sticky wet sensation. 22 Furthermore, the structure and viscoelasticity of coacervates are closely related to the encapsulation and release efficiency of actives compounds 28 as well as their skin adhesion properties. Thus, understanding the phase behavior, structure, and rheological properties of coacervates is of great practical importance for the development of personal care formulations.…”
Section: Introductionmentioning
confidence: 99%
“…A spontaneous liquid/liquid phase separation forms a dense coacervate phase and a dilute equilibrium phase. The coacervates can be created even at surfactant concentrations below the critical micelle concentration and may be stabilised by electrostatic attraction between oppositely charged molecules [31][32][33]. Henceforth, a negatively charged surfactant, sodium dodecyl sulfate (SDS), was utilised to form strong bonds with cationic chitosan, developing insoluble coacervates.…”
Section: Introductionmentioning
confidence: 99%